KEBIJAKAN PENCEGAHAN PELECEHAN SEKSUAL TERHADAP ANAK: MASUKAN BAGI PRAKTISI SOSIAL - Nuryana, Mu’man (Sosio Informa, 2004)
Children Sexual Abuse Prevention Policy: An Input for Practitioners. Many literatures show that there are no differences of background in term of socioeconomic of victims and perpetrators of sexual abuse in family and community. It’s also give information that victim of sexual abuse is categorized as a "silent disease" because of difficulty on obtaining epidemiological data and research on sexual abuse issue is still neglected. However, the literatures showed that sexual abuse causing heavy post-traumatic syndrome and generating problems of social pathology, psychology, emotional, bouncing, physical, and educational in the long term to all victims of in school environment, family, social relation, and participation in community. Therefore, it’s a growing need to plan and develop a policy for training and workshop for teachers and social workers to increase their awareness of the possibility of sexual abuse in the school and environment.